The influence of prandtl number on flow characteristics of the fume from GMAW welding - Luthfi, Luthfi (Journal of Welding Technology, 2023)
GMAW has become one of the most popular welding methods due to its high productivity in the manufacturing industry. However, there has been agrowing concern about the health effects of the fume produced by this welding method, as it may flow into the breathing zone of the welding operator.In this study, the impact of the Pr number on the behavior of the fume flow produced by GMAW was studied numerically using Computational Fluid Dynamics (CFD) simulation. Navier-Stokes and energy equations in two-dimensional axisymmetric coordinates were used to establish the numerical model for the GMAW fume flow.A transient finite-volume method with non-staggered mesh was applied to solve the numerical model. The numerical simulations were run 2.0 ≤ Pr ≤ 15.0 with other parameters kept constant at Fr = 5.5, Re = 100, and H/X0 = 10. The time series of the spreading distance plotted at various Prnumbers show different types of distances at different stages of the fume flow, the initial maximum, the maximum, and the final distances. When the Pr number is increased from 2.0 to 15.0.the gap between the initial maximum and the maximum distances decreases while the gap between the initial maximum and the final distances decreases.A nonlinear relationship was observed when the initial maximum and final distance data were plotted against the Pr number. The best fit for the initial maximum and the final distance data were obtained using the power of -1/2 and -2/3.